Penerapan Model Pembelajaran Berbasis Masalah Sebagai Upaya Meningkatkan Aktivitas dan Hasil Belajar Siswa Pada Materi Suhu dan Kalor - Dina Wulan Suci Rahadiyani; Putri Ayu Rivani; Florentina Untari (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This study aims to determine whether learning using the Problem-Based Learning model can increase student activity and learning outcomes in class X heat and temperature material, especially class XB SMA Xaverius 2 Jambi. Methodology: This research is a classroom action research carried out in three cycles. The types of data in this study were qualitative and quantitative data collected through formative tests and observations of teacher and student activities through observation sheets. Main Findings: The results showed that using the Problem-Based Learning learning model increased student learning activities and resulted in each cycle. In cycle I, the average proportion of student activity was 69.07%. In cycle II, it was 79.85%, and in cycle III, it was 86.88%. Novelty/Originality of this study: Research by applying the Problem-Based Learning learning model in physics learning to increase student activity and learning outcomes on the subject of temperature and heat in class X SMA Xaverius 2 Jambi.